Cognitive abilities and behavioral biases - Oechssler, Joerg; Roider, Andreas; Schmitz, Patrick W. (Discussion paper series, 2008)
We use a simple, three-item test for cognitive abilities to investigate whether established behavioral biases that play a prominent role in behavioral economics and finance are related to cognitive abilities. We find that higher test scores on the Cognitive Reflection Test of Frederick (2005) indeed are correlated with lower incidences of the conjunction fallacy, conservatism in updating probabil-ities, and overconfidence. Test scores are also significantly related to subjects' time and risk preferences. We find no influence on anchoring. However, even if biases are lower for people with higher cognitive abilities, they still remain substantial.
Keywords: Arbeitspapier; Graue Literatur; Investitionsentscheidung; Kognitive Kompetenz; Befangenheit